Incomplete target neutralization by the anti-cancer antibody rilotumumab. Issue 2 (17th February 2016) - Greenall, Sameer A.; Adams, Timothy E.; Johns, Terrance G.
ABSTRACT: The antibody rilotumumab, which has been tested in multiple Phase 2 and Phase 3 trials, has been reported to neutralize hepatocyte growth factor (HGF), the ligand for the oncogene MET. However, we report that rilotumumab does not prevent HGF from directly binding to MET on conventional and primary patient-derived human gliomasphere lines, a trait driven by the HGF α-chain, which remains free to engage cell-surface glycosaminoglycans and the receptor MET. This binding induces MET phosphorylation, initiates robust AKT and ERK signaling and potentiates biological effects such as cell scattering. This partial antagonism was highly exacerbated in the presence of activated epidermal growth factor receptor, which is common in several cancers. Hence, we confirm that rilotumumab is only a partial antagonist of HGF activity, a finding that has considerable implications for the therapeutic use of rilotumumab.